PRINSIP KESANTUNAN DALAM FILM MARMUT MERAH JAMBU KREATOR RADITYA DIKA - Purwi Riswanti; Laurensius Salem; Deden Ramdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract The film was chosen as the object of study because it is an audio visual media that can be witnessed directly by the characters who speak and the response of the speakers in the film. The purpose of this research is to describe the forms of compliance and deviations in the politeness of language, and the application in teaching materials in schools through film media. Politeness is a rule of behavior that is determined and agreed upon by a certain community in social life. This research was conducted in descriptive method. The form of this research was qualitative research. The source of the data was focused on Marmut Merah Jambu movie, therefore the analysed data was the speech of the characters. This study contained 62 data from 33 speech data that obeyed the politeness principle and 29 speech data that violated the politeness principle. The results showed that more speeches obeyed the principle of politeness in language. The deviations of politeness principle were wisdom maxim, generosity maxim, appreciation maxim, simplicity agreement maxim, and sympathy maxim. The speech of the characters in Marmut Merah Jambu movie could be a learning material at school on Grade X odd semester on “Anecdote Text”. Keywords: Language